Cannabidiol can improve complex sleep‐related behaviours associated with rapid eye movement sleep behaviour disorder in Parkinson's disease patients: a case series. (21st May 2014) - Chagas, M. H. N.; Eckeli, A. L.; Zuardi, A. W.; Pena‐Pereira, M. A.; Sobreira‐Neto, M. A.; Sobreira, E. T.; Camilo, M. R.; Bergamaschi, M. M.; Schenck, C. H.; Hallak, J. E. C.; Tumas, V.; Crippa, J. A. S.
Summary What is known and objective Cannabidiol (CBD) is the main non‐psychotropic component of the Cannabis sativa plant. REM sleep behaviour disorder (RBD) is a parasomnia characterized by the loss of muscle atonia during REM sleep associated with nightmares and active behaviour during dreaming. We have described the effects of CBD in RBD symptoms in patients with Parkinson's disease. Cases summary Four patients treated with CBD had prompt and substantial reduction in the frequency of RBD‐related events without side effects. What is new and conclusion This case series indicates that CBD is able to control the symptoms of RBD.